1976
DOI: 10.1289/ehp.76141
|View full text |Cite
|
Sign up to set email alerts
|

Properties and applications of pyrethroids.

Abstract: Improved understanding of the factors determining the insecticidal activity, the mammalian toxicity, and the stability in air and light of natural and synthetic pyrethroids has led to a series of new compounds with a very favorable combination of properties. Their characteristicsinclude outstanding potency to insects, low toxicity to mammals associated with rapid metabolic breakdown and, in appropriate cases, adequate stability on plant surfaces even in bright sunlight. Initial tests indicate that even the mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 52 publications
0
17
0
3
Order By: Relevance
“…In the early 1970s, ITNs emerged as a vector control idea because many communities were already sleeping under untreated bed nets. At this time, synthetic pyrethroids were developed (permethrin, cypermethrin, and deltamethrin), which were safe to use for impregnation of ITNs [118]. Following pioneering trials on ITNs, including those in The Gambia in the 1980s that showed huge impacts on malaria infection and mortality [119][120][121], WHO recommended the use of ITNs for children and pregnant women [122].…”
Section: Gmep Abandoned-what Next For Malaria?mentioning
confidence: 99%
“…In the early 1970s, ITNs emerged as a vector control idea because many communities were already sleeping under untreated bed nets. At this time, synthetic pyrethroids were developed (permethrin, cypermethrin, and deltamethrin), which were safe to use for impregnation of ITNs [118]. Following pioneering trials on ITNs, including those in The Gambia in the 1980s that showed huge impacts on malaria infection and mortality [119][120][121], WHO recommended the use of ITNs for children and pregnant women [122].…”
Section: Gmep Abandoned-what Next For Malaria?mentioning
confidence: 99%
“…The activity of synthetic pyrethroids against insect pests has represented a degree of potency not previously demonstrated in any class of insecticides (Elliott 1976(Elliott , 1980. This order of magnitude increase in potency has accounted for greater efficacy and also for lower rates of application (Herve 1985).…”
Section: Pyrethroid Toxicitymentioning
confidence: 99%
“…Compared to natural pyrethrin, synthetic pyrethroids are much more stable and have, therefore, been widely used in agriculture to control a variety of pests [8]. Investigations on the potential of ITNs to control malaria started during the 1980s [2, 9].…”
Section: Introductionmentioning
confidence: 99%